BOOK REVIEW Abu Hamid (Imam) Al-Ghazali (reprint, 1993) Ihya Ulum Id-Din (Revival of Religious Thought) Volume 3: The Book of Destructive Evils. Trans. Fazlur Karim. Darul Ishat, Urdu Bazar, Karachi - Pakistan - Choudhury, Masud (University of Darussalam Gontor Press, 2024)
This book provides a review of the book “Ihya Ulum Id-Din (Revival of Religious Thought Volume 03)” the work of Islamic scholar Imam Abdul Hamid Al-Ghazali (Imam Ghazali Translated by Fazlul Karim. Darul Ishaat, Urdu Bazar, Karachi, Pakistan, 1993. This is an original contribution, explained in informative content and written in clear language that is accessible to knowledgeable readers.